Mineralogical characteristics of the heterolithic formations from the Carpathian Foredeep Miocene sediments, south-eastern Poland - Przelaskowska, Anna; Zagórska, Urszula; Urbaniec, Andrzej; Łykowska, Grażyna; Klaja, Jolanta; Grela, Jacek; Kędracka, Katarzyna (Geology, Geophysics and Environment, 2022)
Heterolithic complexes from the Carpathian Foredeep are a subject of growing attention as many natural gas accumulations of industrial importance have been discovered in such formations during the last decades. The aim of the presented work was to determine lithotypes of different lithology and mineralogical composition in the heterolithic sequences. Individual lithotypes were distinguished of macroscopic observations of cores, X-ray diffraction analysis (XRD) and X-ray fluorescence method (XRF). Preliminary distinction of the lithotypes was based on macroscopic observations of the core samples. Correlation plots between the contents of particular minerals (XRD analyses) and corresponding elements (XRF analyses) were used for verification of the lithotypes distinguished on the basis of macroscopic observations. Swelling properties of the investigated rocks were determined using the cation exchange capacity (CEC) values. The following lithotypes were identified: medium- to fine-grained sandstones, fine- to very fine-grained sandstones, clayey sandstones, sand-dominated heteroliths, heteroliths with equal proportions of sandstones and mudstones, mud-dominated heteroliths, mudstones, clayey shales. Such division provides a basis for precise petrophysical characterization of the analyzed profiles, that is assignment of particular petrophysical parameters values to individual lithotypes. More reliable petrophysical parameters in the geophysical interpretation of heterolithic sequences allow for a more precise determination of zones characterized by good reservoir parameters.